Jointly cross-layer scheduling and dynamic resource allocation for RT and NRT traffic types for IEEE802.16e - Nascimento, A.
Mobile communications has witnessed an exponential increase in the amount of users, services and applications. New high bandwidth consuming applications are targeted for B3G networks raising more stringent requirements for Dynamic Resource Allocation (DRA) architectures and packet schedulers that must be spectrum efficient and deliver QoS for heterogeneous applications and services. In this paper we propose a new cross layer-based architecture framework embedded in a newly designed DRA architecture for the Mobile WiMAX standard. System level simulation results show that the proposed architecture can be considered a viable candidate solution for supporting mixed services in a cost-effective manner in contrast to existing approaches.